Exploring groundwater resources in southwestern Nigeria: An integrated geophysical approach - I.O. Idowu; A.O. Ojo (HydroResearch)
Groundwater potential regions were delineated using Very-Low Frequency Electromagnetic (VLF-EM) and Vertical Electrical Sounding (VES) geophysical techniques. The VLF-EM measurements were taken as fast reconnaissance to delineate shallow conductive features along seven traverses with 10 m station intervals. The data were qualitatively analyzed and indicated zones of hydrogeological relevance, pointing to regions for VES investigations. Thirteen VESs were mapped with 100 m intervals between current electrodes, and the data were processed manually and using WinResist software to generate sounding curves and geo-electric sections that revealed 3 (84.6%) and 4 (15.4%) layers of earth models. The aquifer units were found in the weathered and fractured layers. The subsurface was classified into high, medium, and low groundwater potential regions, with a larger area indicating low prospects. Regions with high potentials had overburden thicknesses above 18 m, while medium and low yields had overburden thicknesses of 13–18 m and below 13 m, respectively.